Penerapan Root Cause Analysis (RCA) dalam Meningkatkan Kualitas Pelayanan Kesehatan: Literature Review - Tuanku Banang Rabbani Imsyaamru; Salsabila Firdausi; Acim Heri Iswanto (CENDEKIA : Jurnal Penelitian dan Pengkajian Ilmiah, 2026)
The quality of healthcare services and patient safety are critical aspects of healthcare delivery. Various patient safety incidents and quality-related problems continue to occur, most of which are caused by system failures rather than individual errors. Root Cause Analysis (RCA) is a systematic method used to identify the underlying causes of incidents, enabling preventive and sustainable improvement efforts. This study aims to identify, analyze, and synthesize research findings related to the implementation of RCA in improving healthcare service quality. A literature review method was applied by searching articles from Google Scholar, PubMed, ScienceDirect, Springer, and Sage Journals. Eight relevant articles published between 2023 and 2026 were included, focusing on RCA, patient safety, healthcare service quality, quality management, and continuous improvement. The findings indicate that RCA implementation is effective in enhancing patient safety, improving service processes, reducing errors and waste, and supporting organizational learning and quality management. However, several challenges remain, including limited resources, lack of training, increased workload for healthcare professionals, and insufficient follow-up of RCA recommendations. Therefore, strong managerial support, continuous RCA training, and the development of a non-blaming patient safety culture are essential to optimize RCA implementation as a strategy for improving healthcare service quality.